2007
DOI: 10.1111/j.1365-2494.2007.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixing whole‐crop pea–oat silage and grass–clover silage: positive effects on intake and milk production of dairy cows

Abstract: Forty-eight high-yielding dairy cows of the Swedish Red breed were used to examine the effects of providing pea-oat silage (P), grass-clover silage (G) and a 0AE50:0AE50 mixture of the silages (M) ad libitum in diets with two concentrate levels (7 or 10 kg d )1 ). A 9-week experiment, including a 2-week pre-experimental period in which the cows were all fed the same diet, and an in vivo apparent digestibility study were conducted comparing the six dietary treatments (M7, M10, P7, P10, G7, G10). Intake and dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…intakes relative to those consuming grass forage and attributed this to faster rates of fermentation and more rapid particle breakdown and clearance from the rumen (Waghorn et al, 1989;Beever and Thorp, 1996). Moreover, there is evidence to suggest that there is a synergistic effect when a mixture of grass silage and whole-crop cereal silage are offered together relative to either of the silages offered alone (O'Kiely and Moloney, 2002;Keady et al, 2007;Rondahl et al, 2007). Benton et al (2015) reported that corn stalk resulted in better performance than alfalfa or CS when included in a low level in beef finishing diets with 30% wet distillers' grains with solubles, which was owed to the stimulation of physically effective NDF.…”
Section: Discussionmentioning
confidence: 99%
“…intakes relative to those consuming grass forage and attributed this to faster rates of fermentation and more rapid particle breakdown and clearance from the rumen (Waghorn et al, 1989;Beever and Thorp, 1996). Moreover, there is evidence to suggest that there is a synergistic effect when a mixture of grass silage and whole-crop cereal silage are offered together relative to either of the silages offered alone (O'Kiely and Moloney, 2002;Keady et al, 2007;Rondahl et al, 2007). Benton et al (2015) reported that corn stalk resulted in better performance than alfalfa or CS when included in a low level in beef finishing diets with 30% wet distillers' grains with solubles, which was owed to the stimulation of physically effective NDF.…”
Section: Discussionmentioning
confidence: 99%
“…These effects arise from the energy and protein complementarity of the components providing an appropriate balance between readily fermentable nutrients for microbial protein synthesis in the rumen. Furthermore, mixing grain legume-cereal whole-crop silage with grass-clover (Rondahl et al, 2007) or grass (Lamminen et al, 2015) silages may maintain or increase intake and milk production of dairy cows in comparison to conventional grass-based forage rations.…”
Section: Feeding Cattle and Sheepmentioning
confidence: 99%
“…Cereal–legume intercrops silages have been shown to produce higher feed intake and higher N retention than grass silage when offered to ruminants (Adesogan, Salawu, & Deaville, ; Adesogan, Salawu, Williams, Fisher, & Dewhurst, ), making them suitable for use in diets for highly productive ruminants like dairy cows (Rondahl, Bertilsson, & Martinsson, ; Salawu, Adesogan, & Dewhurst, ). Previous studies have compared a few cereal–legume intercrops silages (mainly wheat or barley with pea) in terms of nutritive and fermentation characteristics and found that forage DM yield, fermentation quality and nutritive characteristics may change with growth stage at harvest, legume‐to‐cereal ratio and use of silage additives (Adesogan & Salawu, ; Jacobs & Ward, ; Mustafa & Seguin, ).…”
Section: Introductionmentioning
confidence: 99%